Corrosion behaviour of steel in the presence of rare earth salts: synergistic effect. (25th October 2015) - Mohammedi, D.; Ismail, F.; Rehamnia, R.; Bensalem, R.; Savadogo, O.
Abstract : In this work, the inhibition behaviour of rare earth (RE) salts (Y(NO3 )3 .6H2 O, CeCl3 .7H2 O) in conjunction with metasilicates (Na2 SiO3 .5H2 O) for carbon steel A37 and in aerated 3%NaCl solutions has been investigated. Corrosion inhibition power evaluation and surface layer characterisation have been carried out by electrochemical measurements (potentiodynamic polarisation and impedance) followed by X-ray photoelectron spectroscopy. It was demonstrated that the binary RE/ improved the protective role of oxide/hydroxide films formed on the steel. Electrochemical tests showed that the cathodic and anodic reactions were both inhibited to some extent, leading to a decreased rate of the global corrosion process. The maximum protective inhibition against corrosion attack was evident when an RE/ ion mixture was added. Surface analysis revealed the diverse nature of inhibitor coverage on the steel.